2012
DOI: 10.5402/2012/953461
|View full text |Cite
|
Sign up to set email alerts
|

Acute Phase Reactants as Novel Predictors of Cardiovascular Disease

Abstract: Acute phase reaction is a systemic response which usually follows a physiological condition that takes place in the beginning of an inflammatory process. This physiological change usually lasts 1-2 days. However, the systemic acute phase response usually lasts longer. The aim of this systemic response is to restore homeostasis. These events are accompanied by upregulation of some proteins (positive acute phase reactants) and downregulation of others (negative acute phase reactants) during inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 234 publications
1
70
0
4
Order By: Relevance
“…One possibility for the effect of ribose-cysteine on Lp(a) is that the apo(a) transgene, which is under the control of a transferrin promoter, could be affected. Transferrin is a negative acute phase response protein regulated by inflammatory cytokines [43], the levels of which could be altered by the antioxidant effects of ribosecysteine. However, this possibility seems unlikely given that there was no significant change in apo(a) levels in the livers of ribosecysteine treated animals (Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility for the effect of ribose-cysteine on Lp(a) is that the apo(a) transgene, which is under the control of a transferrin promoter, could be affected. Transferrin is a negative acute phase response protein regulated by inflammatory cytokines [43], the levels of which could be altered by the antioxidant effects of ribosecysteine. However, this possibility seems unlikely given that there was no significant change in apo(a) levels in the livers of ribosecysteine treated animals (Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…This estimate yielded 5 major acute‐phase glycoproteins that were then shown to produce GlycA signals in proportion to their glycan N ‐acetyl glucosamine concentrations (J. Otvos, PhD, LipoScience Inc, personal communication, 2014). Their findings indicate that α1‐acid glycoprotein, haptoglobin, α1‐antitrypsin, α1‐antichymotrypsin, and transferrin—all of which have been implicated in the development of CVD—make major contributions to the GlycA signal. Biomarker profiling by NMR spectroscopy in an Estonian Biobank study found α1‐acid glycoprotein to be significantly predictive of cardiovascular mortality, a finding that was validated in a replication cohort .…”
Section: Discussionmentioning
confidence: 99%
“…CREBH has been shown to directly activate the transcription of acute-phase genes encoding SAP and CRP upon exposure to the pro-inflammatory cytokines IL-1β and IL-6 [22]. Although apoB has not been classified as an APR gene, an early and consistent increase of plasma VLDL has been observed during APR [32, 33]. Our study demonstrated that the CREBH-apoB axis is the signaling pathway that, at least partially, mediated upregulation of VLDL in APR induced by TNFα and LPS.…”
Section: Resultsmentioning
confidence: 99%